State party reporting and the realisation of children's rights in Africa - Remember Miamingi
Human rights norms will largely remain hollow if they are not translated into the lived realities of people on the ground. Given the diversity and complexities of human rights norms, the arrays of institutions, mechanisms and resource required to give full effect to these norms, implementation of human rights norms is a continuous and progressive undertaking. Progress, to be meaningful, should have milestones and mechanisms for tracking it. The reporting mechanisms are human rights' monitoring and evaluation plans and systems to track progressive implementation. This book provides an assessment of the reporting mechanisms of child rights treaty bodies. It highlights what is working or not working and why, making recommendations for further improvement of the reporting mechanism to better work for children in Africa. The findings and recommendations in the book are based on a study commissioned by the Centre for Human Rights, to assess the effects of reporting to United Nations and African Union child rights treaty bodies on the enjoyment of rights, protection and welfare of children in Africa. It covers 17 African countries, and provides a historical snapshot of the situation as at the end of 2017.